EFEKTIVITAS PENEGAKAN HUKUM PENYALAHGUNAAN FUNGSI TROTOAR DI KOTA SINGARAJA BERDASARKAN PERATURAN DAERAH NOMOR 3 TAHUN 2024 - Aisah Kartika Dewi; Made Sugi Hartono; I Gusti Ayu Apsari Hadi (JOURNAL OF LAW AND NATION, 2025)
This study aims to examine and analyze the effectiveness of law enforcement by the Civil Service Police Unit (Satpol PP) of Buleleng Regency regarding the misuse of sidewalks in Singaraja City, based on Buleleng Regency Regional Regulation No. 3 of 2024. The background of this research stems from the high number of sidewalk function violations committed by street vendors (Pedagang Kaki Lima/PKL), which impact the order, safety, and comfort of pedestrians. This research employs an empirical legal method with a descriptive approach. Data were obtained through literature studies and interviews with members of Satpol PP Buleleng. The findings reveal that law enforcement by Satpol PP has not yet been fully effective. This ineffectiveness is influenced by several factors, including weak regulation dissemination, low public awareness, limited resources of Satpol PP, and the public’s negative perception of enforcement actions. Factors influencing the effectiveness of law enforcement include the legal substance, law enforcement apparatus, supporting facilities and infrastructure, public participation, and legal culture. This study recommends strengthening public outreach, enhancing officer capacity, and implementing persuasive yet firm enforcement measures to restore sidewalks to their intended function as safe and comfortable public spaces for pedestrians.